Critical Discourse Analysis of the Manifestations of English Linguistic Challenges: The Case Of The New Draft Language Policy In The South African Police Services - Tebogo Johannes Kekana; Malesela Edward Montle (NUST Journal of Social Sciences and Humanities)
This study explores some of the reasons why, in spite of the recently introduced new draft SAPS Language Policy, the SAPS training programme is not producing police officers with adequate English competency that is relevant to the SAPS workplace. It is argued that the current SAPS Language Policy is not adequately developed as far as the SAPS training programme is concerned. We argue that language policy does not articulate language matters in the SAPS Training Academies and this contributes directly or indirectly to the produce of police officers who are inadequately prepared as far as English competency is concerned. The study argues that language planning agencies in the SAPS have inadvertently or deliberately omitted to include clauses that articulate issues of language as they pertain to the training programme and this is a serious flaw in the whole language policy. Furthermore, we argue that Language policy is a crucial integral part of the SAPS training programme, which without it training will be seriously and dangerously affected. Data were elicited through an analysis of the specifically selected clauses contained in the SAPS draft Language Policy with specific reference to a selected SAPS training Academy in Gauteng province. Discriminant Function Analysis indicated ten interrelated flaws within the SAPS Language policy which has the potential to affect training as far as English competency is concerned. These flaws included the following: the silence of the policy on Assessment, Teaching and Learning in the academy, and the absence of a Teaching and Learning policy to complement the Language policy. Principles from Discourse Analysis and Sentiment Analysis were used as a linchpin in developing the framework for this study. An analysis of the data revealed the following key findings: The study found that the SAPS draft Language police is silent on many fronts for example on the Language of Teaching and Learning, no liaison with the Department of Higher Education and Training (DHET), exclusion of Language Policy in Higher Education Policy (LPHE) as one of the policies forming the legal framework. Lack of pronouncements on issues of pedagogy. The absence of the Teaching and Learning Policy as well as the absence of an Assessment Policy. The findings may help policy makers, SAPS trainers or instructors and curriculum developers for SAPS training academies. The data can also help the Language Management unit of the SAPS.